2017
DOI: 10.3390/polym9050167
|View full text |Cite
|
Sign up to set email alerts
|

A High-Performance Soy Protein Isolate-Based Nanocomposite Film Modified with Microcrystalline Cellulose and Cu and Zn Nanoclusters

Abstract: Soy protein isolate (SPI)-based materials are abundant, biocompatible, renewable, and biodegradable. In order to improve the tensile strength (TS) of SPI films, we prepared a novel composite film modified with microcrystalline cellulose (MCC) and metal nanoclusters (NCs) in this study. The effects of the modification of MCC on the properties of SPI-Cu NCs and SPI-Zn NCs films were investigated. Attenuated total reflectance-Fourier transformed infrared spectroscopy analyses and X-ray diffraction patterns charac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 46 publications
4
21
0
Order By: Relevance
“…The surface morphology of SPI/O@CNF/NS was examined using SEM and EDX tests to study the dispersibility and interfacial interactions of the nanoparticles in SPI matrix. As presented in Figure 4, the pristine SPI exhibits relatively coarse fracture surfaces with numerous holes in accordance with previous reports [10,31], and the silicon content is very small. It is observed that the incorporation of CNF or NS results in a dense and smooth cross-sectional fracture in SPI/CNF or SPI/NS due to the CNF or NS filling the discontinuous matrix and forming interactions with protein for a dense system, while the CNF aggregation in SPI/CNF is owing to the poor interfacial activity of CNF [31].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The surface morphology of SPI/O@CNF/NS was examined using SEM and EDX tests to study the dispersibility and interfacial interactions of the nanoparticles in SPI matrix. As presented in Figure 4, the pristine SPI exhibits relatively coarse fracture surfaces with numerous holes in accordance with previous reports [10,31], and the silicon content is very small. It is observed that the incorporation of CNF or NS results in a dense and smooth cross-sectional fracture in SPI/CNF or SPI/NS due to the CNF or NS filling the discontinuous matrix and forming interactions with protein for a dense system, while the CNF aggregation in SPI/CNF is owing to the poor interfacial activity of CNF [31].…”
Section: Resultssupporting
confidence: 91%
“…As presented in Figure 4, the pristine SPI exhibits relatively coarse fracture surfaces with numerous holes in accordance with previous reports [10,31], and the silicon content is very small. It is observed that the incorporation of CNF or NS results in a dense and smooth cross-sectional fracture in SPI/CNF or SPI/NS due to the CNF or NS filling the discontinuous matrix and forming interactions with protein for a dense system, while the CNF aggregation in SPI/CNF is owing to the poor interfacial activity of CNF [31]. The integration of CNF and NS shows a desired synergistic effect in SPI, which effectively improves the dispersion of CNF and forms an even and uniform fracture in SPI/CNF/NS.…”
Section: Resultssupporting
confidence: 91%
“…As shown in Fig. a, the characteristic amide bands of the SPI‐based films were observed at 1,645, 1,544, and 1,238 cm −1 respectively, which were assigned to Amide I (C=O stretching), Amide II (N − H bending), and Amide III (C − N and N − H stretching) of the protein peptide . The absorption peak at 2,933 cm −1 was attributed to the stretching vibration of −CH 2 group .…”
Section: Resultsmentioning
confidence: 90%
“…The absorption peak of –CH 2 group stretching vibrations was observed at 2933 cm −1 [ 32 ]. The absorption bands at 1399 cm −1 and 1039 cm −1 were attributed to the stretching vibrations of C–H and C–O, respectively [ 33 ]. In particular, the broad band around 3272 cm −1 corresponded to the O–H and N–H stretching vibrations, which were able to form hydrogen bonds with the carbonyl groups in the peptide linkage [ 3 ].…”
Section: Resultsmentioning
confidence: 99%